(untitled) (Research, Society and Development, 2023)
Objective: To describe the profile of individuals who returned to work three years after discharge from the intensive care unit and to determine the predictors of disability upon return to work. Methods: This is a retrospective, quantitative, cross-sectional study of individuals discharged from the intensive care unit (ICU) who had some work activity prior to hospitalization. Data were recorded in two stages: the first, from physiotherapeutic and medical records, and the second, an active search for patients through contact or address collected in the records. Fisher’s exact test was applied to compare categorical data and Phi test was applied to measure the association between variables. Results: The profile of the returning subjects was young individuals (39 ± 17.2 years), who had high Glasgow Coma Scale scores (14 ± 2.2) during hospitalization, who mostly received medical diagnosis related to respiratory and digestive system impairments (28.6%), and who remained on average 7.4 ± 10 days on mechanical ventilation. Conclusion: It was concluded that return to work three years after ICU discharge occurred more frequently in individuals under 40 years of age, who had a satisfactory level of consciousness during hospitalization, and who remained for less time on mechanical ventilation. Moreover, the return to work occurred in individuals with different diagnoses, but those with respiratory and digestive impairments were more frequent.